1995
DOI: 10.1002/bem.2250160308
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and analysis of static magnetic fields that block action potentials in cultured neurons

Abstract: To characterize the properties of static magnetic fields on firing of action potentials (AP) by sensory neurons in cell culture, we developed a mathematical formalism based on the expression for the magnetic field of a single circular current loop. The calculated fields fit closely the field measurements taken with a Hall effect gaussmeter. The biological effect induced by different arrays of permanent magnets depended principally on the spatial variation of the fields, quantified by the value of the gradient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 4 publications
5
53
0
Order By: Relevance
“…A third group of reports describes an inhibition of Ca 2ϩ signaling by strong static MFs in GH3 cells (72) and retardation of metabolic activity in HL60 cells (74), as well as a block of action potentials by static MFs in cultured neurons (11). Similarly, stimulation of cells with MF frequencies apart from the active frequency windows has been shown to act as an inhibitor to prestimulated Ca 2ϩ signaling (87,95).…”
Section: Physiological Effects Of Mf Exposurementioning
confidence: 99%
“…A third group of reports describes an inhibition of Ca 2ϩ signaling by strong static MFs in GH3 cells (72) and retardation of metabolic activity in HL60 cells (74), as well as a block of action potentials by static MFs in cultured neurons (11). Similarly, stimulation of cells with MF frequencies apart from the active frequency windows has been shown to act as an inhibitor to prestimulated Ca 2ϩ signaling (87,95).…”
Section: Physiological Effects Of Mf Exposurementioning
confidence: 99%
“…These results quantitatively show that the particle number and size were not spatially uniform within each cluster. Previous work showing the increased effect of a steep magnetic field gradient on increased neural action potentials (Cavopol et al 1995) suggests that the deposition of more particles toward the edge may be due to the effect of the steep magnetic field gradient in this area where magnets of opposite poles meet. Haverkort et al (2009) have shown that capture efficiency increases with decreasing drag force so that smaller particles will be collected preferentially in the areas of highest field strength.…”
Section: Spatial Distribution Across the Mpas Substratementioning
confidence: 96%
“…Surfaces with opposite poles attract and adhere to each other, while like poles repel. The array of tightly packed small adjacent magnets have close interactions and consist of multiple and alternating magnetic poles that form a steep magnetic field gradient with an inhomogeneous maximum effective region (MER) between adjacent magnets of alternating polarity (Cavopol et al 1995;McLean et al 2001). Iron oxide (Fe 3 O 4 ) particles are paramagnetic (magnetically susceptible) and become nonpermanent magnets in the presence of an electromagnetic field (Jackson 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Many experimental works have shown that static magnetic fields can modulate neuronal physiology (Azanza and Calvo, 2000;Azanza and del Moral, 1994;Cavopol et al, 1995;Coots et al, 2004;Liboff, 1979;Rosen, 2003;Trabulsi et al, 1996;Vargas et al, 2006;Wieraszko, 2000;Ye et al, 2004). Some passive membrane properties of neurones are affected by the exposure to weak static magnetic fields, increasing the magnitude of evoked action potentials and excitatory postsynaptic potentials (Ye et al, 2004).…”
Section: Can Static Astroglial Magnetic Fields Influence Neuronal Actmentioning
confidence: 99%
“…Indeed, McLean and associates showed that it was the magnetic field gradient instead of the intensity, the parameter that greatly affected the firing of cultured neurones (Cavopol et al, 1995). In this regard, it has been shown that fast firing neurones (>17 spikes/s) isolated from the hippocampal formation of homing pigeons, clearly displayed a phasic increase in firing during different ambient magnetic field conditions (Vargas et al, 2006).…”
Section: Can Static Astroglial Magnetic Fields Influence Neuronal Actmentioning
confidence: 99%